Gaya Hidup Brand Minded dan Intensi Membeli Produk Fashion Tiruan Bermerk Eksklusif Pada Remaja Putri - Wijaya, Resti Athhardi; Djalali, M. As’ad; Sofiah, Diah (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2015)
Abstract, The purpose of this study is to determine the relationship between the intention topurchase counterfeit exclusive branded fashion products with brand minded life style. Variablesused in this study consist of the independent variable is brand minded life style (X). While thedependent variable is the intention to purchase counterfeit exclusive branded fashion products (Y).The subject of this study are female adolescents aged between 16 until 19 years in Surabaya. Theanalysis result state that brand minded life style have not significant relationship with the intentionto purchase counterfeit exclusive branded fashion products.Keywords : Brand Minded Life Style, Intention to purchase